The dynamics of formal employment by economic activity sectors in the international border municipalities of Mato Grosso do Sul, Brazil (Desenvolvimento em Questão, 2026)
This study analyzes the dynamics of formal employment by sectors of economic activity in the international border municipalities of Mato Grosso do Sul for the period 2000–2022 and the subperiods 2000–2008, 2008–2016, and 2016–2022. Firstly, the text presents the population dynamics for 2000 and 2022, as well as the dynamics of formal employment by productive sectors in the region in 2000, 2008, 2016, and 2022. Subsequently, the Location Quotient (LQ), Redistribution Coefficient (REDC), and Location Coefficient (LC) are used to identify possible changes in the locational pattern of employment in the region during the analyzed period and its subperiods. The results show that the studied municipalities are quite heterogeneous, both in land area and productive structure, as well as in population size and job creation, with the municipalities of Corumbá and Ponta Porã concentrating 60% of the population and 68.4% of regional jobs in 2022. The results also show that public administration is the region’s main employer, accounting for 23.8% of all jobs in that year. Furthermore, evidence suggests that the locational pattern of employment by economic activity sector underwent changes during the period analyzed, with the sectors of manufacturing, utility services, civil construction, and public administration presenting the most significant spatial changes.
Keywords: employment dynamics; regional measures; municipalities; border; Mato Grosso do Sul